(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
In the context of modern urbanization processes, the priority of sustainable urban development and the actualization of issues of cultural heritage preservation, the revitalization of industrial facilities, in particular historical wineries, is of particular importance. Such complexes form a unique segment of industrial architectural heritage, combining production, cultural and landscape characteristics and closely related to local identity, historical traditions and spatial structure of territories. In the context of the transformation of economic models, deindustrialization and the development of creative industries, former wineries are increasingly being considered as potential centers of socio-cultural activity, tourism, public initiatives and spatial renewal of the urban environment. The aim of the article is to analyze modern approaches and practices of revitalization of historical wineries with a focus on architectural and urban planning directions of adaptive reuse and principles of sustainable development. The study considers key problems of preserving the historical and architectural value of objects, the features of their functional transformation, the formation of new scenarios of use and the integration of modern needs of the community, the market and tourism infrastructure. Special attention is paid to the issues of functional mix, interaction with adjacent urban spaces and the role of revitalized complexes in the formation of a multifunctional urban environment. The evolution of approaches to the revitalization of wineries in European and international practice is summarized, and their potential as a tool for sustainable spatial development and improving the quality of the urban environment is determined. The results obtained can be used in the practice of architectural and urban design, redevelopment of industrial areas and strategic planning of the development of historical production complexes.